Neuromedin U mediates left atrial pressure–induced diuresis in the anaesthetised pig - Vincent Healy; Therese Ruane O’Hora; Eric Lucking; Gerard O’Donoghue; Farouk Markos (PLoS ONE, 2026)
Finding a potential biomarker for elevated left atrial pressure would be clinically useful as a diagnostic for pre-heart failure. Therefore, an investigation into whether the protein neuromedin U (NMU), which is significantly elevated in heart failure patients, mediates a classical diuresis that results from a sustained increase in left atrial pressure was conducted in the anaesthetized pig. Left atrial pressure was increased a little above 15 mmHg for 30 minutes in 8 chloralose anaesthetised female pigs. There was a significant increase in circulating NMU and urine flow rate, which surprisingly occurred without an accompanying natriuresis; both the serum NMU increase and the diuresis did not occur when the procedure was repeated post-vagal section. There was also a significant increase in glomerular filtration rate during the diuresis, which indicates a likely direct renal effect. The results show that NMU could be the mediator of the historic diuresis induced by an increased left atrial pressure. Future work to assess NMU levels in humans in pre-heart failure would be required to confirm NMU’s potential usefulness as a diagnostic.